Webkinz as Consumerist Discourse: A Critical Ideological Analysis - Dellinger-Pate, Charlie; Conforti, Rosemary (High tech tots: Childhood in a digital world, 2010)
Keywords: dept.com

Orson welles, harry alan towers, and the many lives of harry lime - Tavares, Frank (Journal of Radio & Audio Media, 2010)
In 1951, prolific radio producer Harry Alan Towers created The Lives of Harry Lime, a 52-episode series starring Orson Welles. It was based on the character Welles made famous in the popular Carol Reed film, The Third Man. Its success was the result of Towers's aptitude for seeing the untapped marketing potential of an existing fictional character, combined with his facility at working through the legal restrictions, and his ability to convince a reluctant Welles to participate. This article traces the genesis, production, and distribution of the only radio series on which Welles played a recurring dramatic role, and examines Welles's limited involvement in his temporary return to radio well after becoming a filmmaker. © 2010 Broadcast Education Association.
Keywords: dept.com